Alcohol concentrations for determining soil particle density using the volumetric glassware method - Santos, Aline Aparecida dos; Moretti de Souza, Jorge Luiz; Kreutz Rosa, Stefanie Lais (Acta Iguazu, 2020)
The objective of this study was to evaluate the efficiency of alcohol in concentrations of 0.0, 47.6, 70 and 99 °GL, to determine the soil particle density (rp) with the Volumetric Glassware Method (VG), verifying the best time of analysis and the possibility of alternatives to 99 °GL alcohol concentration. The soil samples were collected in five experimental areas of the Fundação ABC (Arapoti, Castro, Itaberá, Ponta Grossa and Tibagi), at 0.0-0.20 m depth, stored in a plastic bag and forwarded to the Soil Physics laboratory of the Federal University of Paraná. Analyzes with alcohol concentrations were performed with five repetitions, for each location, totaling 100 samples. The comparison of the “rp obtained with VG and 99 °GL alcohol” (rpVG.99) vs “rp with alternative methods” (water: rpVG.w; 47.6 °GL alcohol: rpVG.47.6; and 70 °GL alcohol: rpVG.70) values were performed considering linear regression analysis, Box Plot diagram, coefficient of variation (CV) and determination (R2), index of agreement (d) and mean absolute error (MAE). The 70 °GL concentration obtained good associations with the 99 °GL concentration (R2 > 0.82), as well as low values of CV and MAE. The other concentrations analyzed had promising results. For the soils analyzed, the 70 °GL alcohol concentration can replace 99 °GL to obtain rp values with the Volumetric Glassware Modified Method, requiring data readings after 48 h.